Laminate and method for producing the same
Patent Information
- Application Number
- JP2023135598
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
Smart Images

Figure 2025030366000003 
Figure 2025030366000004 
Figure 2025030366000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate and a method for producing the same. [Background technology]
[0002] 4-methyl-1-pentene polymers have low surface tension, excellent releasability, and high heat resistance, and therefore laminates including a layer containing a 4-methyl-1-pentene polymer and a substrate layer are used as industrial release films (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-34258 A [Patent Document 2] JP 2023-73865 A Summary of the Invention [Problem to be solved by the invention]
[0004] Even if a 4-methyl-1-pentene polymer is combined directly with a substrate to form a laminate, the 4-methyl-1-pentene polymer tends to have poor adhesion to the substrate. From the viewpoint of production cost, a laminate that can be produced at an aging temperature close to room temperature (23° C.) is desirable. Therefore, an object of the present disclosure is to provide a laminate which has high adhesion between a base layer and a layer containing a 4-methyl-1-pentene polymer and which has a low aging temperature in the production process, and a production method thereof. [Means for solving the problem]
[0005] One embodiment of the laminate of the present disclosure includes a base layer (I) and a layer (II) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirements (a) to (c), and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A). (a) a melting point (Tm) measured by differential scanning calorimetry (DSC) of greater than 180°C and less than or equal to 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230°C or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by differential scanning calorimetry (DSC) is 210°C or lower. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a laminate having high adhesion between a base layer and a layer containing a 4-methyl-1-pentene polymer and further having a low aging temperature in the production process, and a production method thereof. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view of a laminate according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a laminate according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present disclosure, unless otherwise specified, the expression "A to B" regarding a numerical range means that the range is from A to B. For example, the expression "10 to 20%" means from 10% to 20%. Additionally, the various monomers in the present disclosure may be derived from fossil raw materials or biomass.
[0009] The laminate of the present disclosure will be described in detail below. The laminate of the present disclosure includes a base layer (I) and a layer (II) containing a 4-methyl-1-pentene polymer (A) and an olefin polymer resin (B) other than the 4-methyl-1-pentene polymer (A) that satisfy the following requirements (a) to (c):
[0010] [Base material layer (I)] The substrate layer (I) contains, for example, a thermoplastic resin as a main component. The main component means the component having the largest mass fraction among the components contained in the layer. Examples of the thermoplastic resin include polyolefin, polyester, and polyamide. Examples of the polyolefin include polyethylene, polypropylene, poly-4-methyl-1-pentene, and polybutene. Examples of the polyethylene include high-density polyethylene, medium-density polyethylene, high-pressure low-density polyethylene, and linear low-density polyethylene. Examples of the polyester include polyethylene terephthalate and polyethylene naphthalate. Examples of the polyamide include polyamide 6, polyamide 66, polyamide 12, and polyamide 6-66 copolymer.
[0011] The thermoplastic resin may be one type or two or more types. The content of the thermoplastic resin in the base layer (I) is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The substrate layer (I) may be a single layer or a multi-layer structure.
[0012] From the viewpoint of adhesion to the layer (II), the base layer (I) preferably contains a polyolefin, more preferably polyethylene and / or polypropylene, and further preferably polypropylene.
[0013] Examples of polypropylene include homopolymers of propylene and copolymers mainly containing structural units derived from propylene. When polypropylene is a copolymer, it may be a random copolymer or a block copolymer. Examples of monomers that copolymerize with propylene include α-olefins other than propylene and diene compounds.
[0014] The content of structural units derived from propylene in the polypropylene (hereinafter also referred to as "propylene content") is preferably 85 to 100 mol %, more preferably 90 to 100 mol %. When polypropylene is a copolymer, the propylene content in the copolymer is preferably 90 to 99.5 mol %, and the content of other monomers (the content of structural units derived from monomers other than propylene) is preferably 0.1 to 15 mol %, more preferably 0.5 to 10 mol %.
[0015] Examples of the α-olefins other than propylene include α-olefins having 2 to 20 carbon atoms (excluding propylene), such as ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, and 1-tetradecene. Examples of polypropylene include propylene homopolymer, propylene-ethylene random copolymer, propylene-1-butene random copolymer, propylene-1-butene-ethylene random copolymer, propylene-1-hexene random copolymer, propylene-3-methyl-1-butene random copolymer, and propylene-4-methyl-1-pentene random copolymer.
[0016] The polypropylene may be used alone or in combination of two or more kinds. Polypropylene can be produced by polymerizing monomers in the presence of known catalysts such as Ziegler-Natta catalysts and metallocene catalysts by known polymerization methods such as gas phase, bulk and slurry methods.
[0017] The MFR of polypropylene measured in accordance with ASTM D 1238 at 230° C. under a load of 2.16 kg is preferably 0.1 to 100 g / 10 min, more preferably 0.3 to 30 g / 10 min, further preferably 0.5 to 20 g / 10 min, and particularly preferably 1.0 to 10 g / 10 min. When the base layer (I) contains polypropylene, the content of polypropylene in the base layer (I) is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0018] The substrate layer (I) contains a polyolefin having a melting point (Tm) of preferably 200° C. or less, more preferably 180° C. or less, and even more preferably 170° C. or less. The melting point of the polyolefin is preferably 120° C. or more, more preferably 130° C. or more, even more preferably 140° C. or more, and particularly preferably 150° C. or more. Polyolefins having a melting point (Tm) within the above range can be formed into a film that serves as a substrate, and can be used as a general-purpose substrate for packaging materials and the like. The melting point (Tm) is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section.
[0019] Examples of the method for forming the base layer (I) include extrusion molding methods such as the T-die method and the extrusion tubular method (inflation method), solution casting method, and calendar molding method. The T-die method is preferred as the method for forming the base layer (I) from the viewpoint of maintaining a uniform film thickness. The surface of the substrate layer (I) which comes into contact with the layer (II) may be subjected to a conventionally known surface treatment such as a corona treatment or a roughening treatment.
[0020] The thickness of the substrate layer (I) is preferably 10 to 500 μm, more preferably 15 to 400 μm, even more preferably 20 to 300 μm, still more preferably 25 to 200 μm, and particularly preferably 30 to 150 μm. The thickness of the substrate layer (I) is measured, for example, by observing the cross section of the laminate in a direction perpendicular to the surface of the laminate with a scanning electron microscope (SEM).
[0021] The substrate layer (I) may contain, for example, additives such as other resins, tackifiers, weather stabilizers, heat stabilizers, antistatic agents, antislip agents, antiblocking agents, lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, and antioxidants. The substrate layer (I) may contain one or more additives.
[0022] The substrate layer (I) may be, for example, a substrate film. The substrate film may contain, for example, a thermoplastic resin, and may contain additives as desired. The substrate film may be produced, for example, by an extrusion molding method such as a T-die casting method and an inflation molding method, or a solution casting method. The substrate film may be stretched. The substrate film may be, for example, a uniaxially stretched film or a biaxially stretched film. The substrate film may be a single layer or a multilayer.
[0023] [Layer (II)] The layer (II) contains a 4-methyl-1-pentene polymer (A) and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A). From the viewpoint of adhesion between the base layer (I) and the layer (II), the layer (II) contains preferably 100 to 4,000 parts by mass, more preferably 120 to 3,900 parts by mass, even more preferably 130 to 3,800 parts by mass, still more preferably 150 to 3,700 parts by mass, and particularly preferably 160 to 3,650 parts by mass of the olefin polymer (B) per 100 parts by mass of the 4-methyl-1-pentene polymer (A).
[0024] The surface free energy of the layer (II) on the side opposite to the surface facing the base layer (I) is preferably 32 mN / m or less, more preferably 30 mN / m or less, and even more preferably 28 mN / m or less. The lower limit of the surface free energy is preferably 15 mN / m, more preferably 20 mN / m.
[0025] The thickness of the layer (II) is preferably 0.01 to 20 μm, more preferably 0.03 to 10 μm, further preferably 0.05 to 5 μm, and particularly preferably 0.1 to 3 μm. When the thickness of the layer (II) is within the above range, even if the layer (II) is formed only on one side of the base layer (I), the laminate is less likely to curl. Furthermore, when the thickness of the layer (II) is within the above range, even if the base layer (I) does not have a multilayer structure provided with an intermediate layer for suppressing curling, the laminate is less likely to curl. The thickness of the layer (II) is measured, for example, by observing a cross section of the laminate in a direction perpendicular to the surface of the laminate with a scanning electron microscope (SEM).
[0026] <4-methyl-1-pentene polymer (A)> The 4-methyl-1-pentene polymer (A) contains a structural unit derived from 4-methyl-1-pentene. The 4-methyl-1-pentene polymer (A) may further contain a structural unit derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene).
[0027] In the following description, in the 4-methyl-1-pentene polymer (A), the structural unit derived from 4-methyl-1-pentene may be referred to as "structural unit (i)", and the structural unit derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) may be referred to as "structural unit (ii)". The 4-methyl-1-pentene polymer (A) may be referred to as "polymer (A)".
[0028] Examples of α-olefins from which the structural unit (ii) is derived include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene.
[0029] The α-olefin from which the structural unit (ii) is derived is preferably an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene), more preferably 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, and 1-octadecene, and even more preferably 1-decene, 1-hexadecene, and 1-octadecene. Polymer (A) containing structural unit (ii) derived from an α-olefin having 6 to 18 carbon atoms tends to have excellent heat resistance.
[0030] The structural unit (ii) may be a structural unit derived from one type selected from α-olefins having 2 to 20 carbon atoms, or may be a structural unit derived from two or more types selected from α-olefins having 2 to 20 carbon atoms.
[0031] In the polymer (A), the content (U1) of the structural unit (i) is preferably 84 to 100 mol%, more preferably 86 to 99 mol%, even more preferably 90 to 98 mol%, and particularly preferably 93 to 98 mol%, and the content (U2) of the structural unit (ii) is preferably 0 to 16 mol%, more preferably 1 to 14 mol%, even more preferably 2 to 10 mol%, and particularly preferably 2 to 7 mol% (wherein the sum of U1 and U2 is 100 mol%). U1 and U2 were measured using the apparatus and conditions described in the Examples. 13 It can be calculated by measuring the C-NMR spectrum. The polymer (A) in which U1 and U2 fall within the above ranges tends to have excellent heat resistance.
[0032] The polymer (A) satisfies the following requirements (a) to (c).
[0033] <Requirement (a)> The melting point (Tm) of the polymer (A) is greater than 180°C and equal to or lower than 220°C. The melting point (Tm) is preferably 184 to 217° C., more preferably 186 to 215° C., and further preferably 188 to 215° C. The polymer (A) having a melting point (Tm) within the above range has excellent heat resistance, and therefore the layer (II) containing the polymer (A) also tends to have excellent heat resistance.
[0034] The melting point (Tm) tends to depend on the stereoregularity of the polymer (A) and the content of the structural unit (ii). Therefore, for example, the melting point (Tm) can be adjusted by using an olefin polymerization catalyst described later and further controlling the content of the structural unit (ii). The melting point (Tm) is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section.
[0035] <Requirement (b)> The endothermic end temperature (TmE) in the melting (endothermic) curve of the polymer (A) is 230° C. or lower. The endothermic end temperature (TmE) is preferably less than 230°C, more preferably 228°C or less, and even more preferably less than 228°C. The lower limit of the endothermic end temperature (TmE) is preferably 190°C. The endothermic end temperature means the temperature at which melting is completed. The endothermic end temperature and the exothermic start temperature described below are indexes different from the onset and offset, which are generally the intersection points between the baseline and the tangent to the steady line. The endothermic end temperature (TmE) is measured by DSC, and the details of the measurement method are described in the Examples section.
[0036] The polymer (A) having an endothermic end temperature (TmE) in the above range has excellent heat resistance. Therefore, the layer (II) containing the polymer (A) also tends to have excellent heat resistance. The polymer (A) having an endothermic end temperature (TmE) in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a 4-methyl-1-pentene polymer having an endothermic end temperature (TmE) outside the above range. Therefore, the properties of a coating agent prepared using the polymer (A) having an endothermic end temperature (TmE) in the above range tend to be uniform.
[0037] The endothermic end temperature (TmE) can be adjusted, for example, by appropriately selecting an olefin polymerization catalyst when producing the polymer (A) and by controlling the content of the structural unit (ii).
[0038] <Requirement (c)> The polymer (A) has an exothermic onset temperature (TcS) in the crystallization (exothermic) curve of 210° C. or lower. The heat generation onset temperature means the temperature at which heat generation begins. The heat generation onset temperature (TcS) is 210° C. or lower, preferably lower than 210° C., more preferably lower than 200° C., and even more preferably lower than 200° C. The lower limit of the heat generation onset temperature (TcS) is preferably 160° C. The exotherm onset temperature (TcS) can be adjusted, for example, by appropriately selecting an olefin polymerization catalyst when producing the polymer (A) and by controlling the content of the structural unit (ii).
[0039] The polymer (A) having a heat generation onset temperature (TcS) within the above range has excellent heat resistance. Therefore, the layer (II) containing the polymer (A) also tends to have excellent heat resistance. The polymer (A) having a heat generation onset temperature (TcS) within the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a 4-methyl-1-pentene polymer having a heat generation onset temperature (TcS) outside the above range. Therefore, the properties of a coating agent prepared using the polymer (A) having a heat generation onset temperature (TcS) within the above range tend to be uniform. The heat generation onset temperature (TcS) is measured by DSC, and the details of the measurement method are described in the Examples section.
[0040] Since the polymer (A) satisfies the requirements (a) to (c), it has excellent solubility in a solvent while maintaining heat resistance. In addition, since the polymer (A) that satisfies the requirements (a) to (c) has excellent solubility in a solvent, it is easy to maintain a dissolved state in the solvent. Therefore, the polymer (A) that satisfies the requirements (a) to (c) has good storage stability when dissolved in a solvent, compared with a 4-methyl-1-pentene polymer that does not satisfy one or more of the requirements (a) to (c).
[0041] The polymer (A) preferably has an intrinsic viscosity [η] of 0.5 to 5.0 dl / g as measured in decalin at 135° C. The intrinsic viscosity [η] is more preferably 0.65 to 4.0 dl / g, and even more preferably 0.8 to 3.0 dl / g. The polymer (A) having an intrinsic viscosity [η] within the above range has excellent heat resistance. A coating agent containing the polymer (A) having an intrinsic viscosity [η] within the above range has excellent coatability and is suitable for forming the layer (II).
[0042] The intrinsic viscosity [η] can be adjusted, for example, by the amount of hydrogen added in the polymerization step when producing the polymer (A). The intrinsic viscosity [η] can be calculated by measuring the specific viscosity under the conditions described in the Examples.
[0043] The crystallization temperature (Tc) of the polymer (A) is preferably from 110 to 200°C, more preferably from 120 to 195°C, and further preferably from 130 to 190°C. The crystallization temperature (Tc) can be adjusted, for example, by appropriately selecting an olefin polymerization catalyst when producing the polymer (A) and by controlling the content of the structural unit (ii). The polymer (A) having a crystallization temperature within the above range is excellent in heat resistance and moldability. The crystallization temperature (Tc) is measured by DSC, and the details of the measurement method are described in the Examples section.
[0044] The polymer (A) may be a graft-modified 4-methyl-1-pentene polymer that has not been graft-modified, or may be a graft-modified 4-methyl-1-pentene polymer (hereinafter also referred to as a "graft-modified 4-methyl-1-pentene polymer"). The graft-modified 4-methyl-1-pentene polymer can be obtained, for example, by graft-modifying a 4-methyl-1-pentene polymer that has not been graft-modified with an ethylenically unsaturated monomer.
[0045] Examples of ethylenically unsaturated monomers include unsaturated compounds having one or more carboxylic acid groups, esters of unsaturated compounds having one or more carboxylic acid groups and alkyl alcohols, and unsaturated compounds having one or more carboxylic acid anhydride groups. Examples of the unsaturated group contained in the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group.
[0046] The ethylenically unsaturated monomer is preferably an unsaturated dicarboxylic acid or an acid anhydride thereof, more preferably maleic acid, nadic acid or an acid anhydride thereof. The method of grafting 4-methyl-1-pentene polymer with ethylenically unsaturated monomer includes conventionally known graft polymerization methods, such as a solution method and a melt kneading method.Specific examples of the graft polymerization method include a method of melting 4-methyl-1-pentene polymer, adding ethylenically unsaturated monomer to carry out graft reaction, and a method of dissolving 4-methyl-1-pentene polymer in a solvent to prepare a solution, adding ethylenically unsaturated monomer thereto to carry out graft reaction. The ethylenically unsaturated monomer may be used alone or in combination of two or more kinds.
[0047] The amount of graft modification of the ethylenically unsaturated monomer in the graft modified 4-methyl-1-pentene polymer is preferably 0.1 to 5.0 mass %, more preferably 0.3 to 4.0 mass %, and further preferably 0.5 to 3.0 mass %.
[0048] The graft modification amount means the mass of the structural unit derived from the ethylenically unsaturated monomer used for the graft modification relative to the mass of the graft modified 4-methyl-1-pentene polymer. The graft modification amount is measured by infrared spectroscopy (IR), and specifically, can be determined by the method described in the Examples. When it is difficult to measure the graft modification amount by infrared spectroscopy (IR), the graft modification amount can be determined by the method described in the Examples. 1 It may also be measured by H-NMR.
[0049] The polymer (A) may be a copolymer in which the structural units derived from the polymerizable monomer are only the structural units (i) and (ii). In this case, the total content of the structural units (i) and (ii) is 100 mol % of all the structural units derived from the polymerizable monomers in the polymer (A). In addition to the structural units (i) and (ii), the polymer (A) may further contain structural units derived from other polymerizable monomers other than 4-methyl-1-pentene and α-olefins having 2 to 20 carbon atoms, as long as the amount is small enough not to impair the object of the present disclosure, specifically 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, of 100 mol % of all structural units derived from polymerizable monomers.
[0050] Examples of other polymerizable monomers include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, and vinylcyclohexane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; and non-conjugated polyenes, such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, and 5-methylene-2-norbornene. The constitutional units derived from other polymerizable monomers may be of one type or of two or more types.
[0051] The polymer (A) can be obtained, for example, by polymerizing 4-methyl-1-pentene, optionally together with an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) from which the structural unit (ii) is derived, and optionally together with other polymerizable monomers, in the presence of an olefin polymerization catalyst, by a known method. Examples of the olefin polymerization catalyst that can be used in the production of the polymer (A) include metallocene catalysts.Preferred metallocene catalysts include those described in WO 01 / 53369, WO 01 / 27124, JP-A-3-193796, JP-A-02-41303, WO 06 / 025540, and WO 2014 / 123212.
[0052] <Olefin Polymer (B)> Examples of the olefin polymer (B) other than the 4-methyl-1-pentene polymer (A) include thermoplastic resins. The olefin polymer (B) preferably contains an olefin thermoplastic elastomer.
[0053] An example of an olefin-based thermoplastic elastomer is a polymer containing a structural unit derived from an α-olefin having 2 to 20 carbon atoms (hereinafter, also referred to as “polymer (b)”). The olefin-based thermoplastic elastomer is preferably a modified polymer in which an unmodified polymer containing a structural unit derived from an α-olefin having 2 to 20 carbon atoms is graft-modified with a polar group-containing monomer. The olefin-based thermoplastic elastomer preferably does not contain a structural unit derived from 4-methyl-1-pentene.
[0054] The polymer (b) is not particularly limited as long as it contains a structural unit derived from an α-olefin having 2 to 20 carbon atoms, and may be a polymer made of an α-olefin having 4 to 20 carbon atoms, or a copolymer made of an α-olefin having 4 to 20 carbon atoms and an α-olefin having 2 to 3 carbon atoms, or may be a polymer containing a structural unit derived from an unsaturated monomer other than an α-olefin (hereinafter also referred to as "other unsaturated monomer"). From the viewpoints of the long-term stability of the composition (Y) described below and the adhesion between the layer (I) and the layer (II), the polymer (b) preferably contains a structural unit derived from an α-olefin having 4 to 20 carbon atoms.
[0055] The structural unit in polymer (b) derived from an α-olefin having 2 to 20 carbon atoms may be one type alone or two or more types. That is, polymer (b) may be a homopolymer of an α-olefin having 2 to 20 carbon atoms, a copolymer obtained using the α-olefin, or a copolymer obtained using one or more types of α-olefin having 4 to 20 carbon atoms and one or more types of α-olefin having 2 to 3 carbon atoms. The copolymer includes, for example, a random copolymer and a block copolymer, and is preferably a random copolymer.
[0056] Examples of the α-olefin having 4 to 20 carbon atoms include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. The α-olefin having 4 to 20 carbon atoms is preferably a linear α-olefin having 4 to 10 carbon atoms, more preferably a linear α-olefin having 4 to 6 carbon atoms, and further preferably includes 1-butene, and particularly preferably 1-butene, from the viewpoint of easily obtaining a polymer having excellent solubility in an organic solvent described later.
[0057] Examples of the α-olefin having 2 to 3 carbon atoms include ethylene and propylene. The α-olefin having 2 to 3 carbon atoms preferably includes propylene, and more preferably propylene, from the viewpoint of easily obtaining a polymer having excellent solubility in an organic solvent described later. Other unsaturated monomers include, for example, conjugated dienes such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; and non-conjugated polyenes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, and 5-methylene-2-norbornene.
[0058] From the viewpoint of easily obtaining a polymer having excellent solubility in an organic solvent described later, the polymer (b) is preferably a copolymer obtained by using one or more α-olefins having 4 to 20 carbon atoms and one or more α-olefins having 2 to 3 carbon atoms, more preferably a copolymer of propylene and an α-olefin having 4 to 20 carbon atoms, even more preferably a copolymer in which all structural units except for structural units derived from propylene are structural units derived from an α-olefin having 4 to 20 carbon atoms, still more preferably a copolymer of propylene and an α-olefin having 4 to 20 carbon atoms containing a structural unit derived from 1-butene, and particularly preferably a copolymer of 1-butene and propylene.
[0059] In the polymer (b), the content of the structural units derived from an α-olefin having 4 to 20 carbon atoms is preferably 5 to 60 mol% relative to 100 mol% of all structural units derived from polymerizable monomers. The lower limit of the above range is preferably 5 mol%, more preferably 10 mol%, and even more preferably 20 mol%. The upper limit of the content of the structural units derived from an α-olefin having 4 to 20 carbon atoms is preferably 60 mol%, more preferably 50 mol%, even more preferably 40 mol%, and particularly preferably 35 mol%. When the content of the structural unit derived from an α-olefin having 4 to 20 carbon atoms is equal to or less than the upper limit, the polymer (b) has excellent strength, and therefore the layer (II) containing the polymer (b) also has excellent strength. When the content of the structural unit derived from an α-olefin having 4 to 20 carbon atoms is equal to or more than the lower limit, the polymer (b) has excellent solubility in an organic solvent described later.
[0060] In the polymer (b), the content of the structural units derived from an α-olefin having 2 to 3 carbon atoms is preferably 40 to 95 mol% relative to 100 mol% of all structural units derived from polymerizable monomers. The lower limit of the above range is preferably 40 mol%, more preferably 50 mol%, even more preferably 60 mol%, and particularly preferably 65 mol%. The upper limit of the content of the structural units derived from an α-olefin having 2 to 3 carbon atoms is preferably 95 mol%, more preferably 90 mol%, and even more preferably 80 mol%. When the content of the structural units derived from an α-olefin having 2 to 3 carbon atoms is less than or equal to the above upper limit, the melting point (Tm) and heat of fusion of polymer (b) can be reduced. When the content is more than or equal to the above lower limit, a polymer containing structural units derived from an α-olefin having 2 to 20 carbon atoms has excellent strength, and therefore layer (II) containing polymer (b) also has excellent strength.
[0061] The heat of fusion (ΔH) of the polymer (b) is preferably 0 to 30 J / g. The heat of fusion (ΔH) of the polymer (b) is preferably 0 J / g or more, more preferably 3 J / g or more, even more preferably 5 J / g or more, and preferably 40 J / g or less, more preferably 35 J / g or less, even more preferably 30 J / g or less. It is also preferable that ΔH is 0 J / g.
[0062] A polymer (b) having a ΔH within the above range can be obtained, for example, by appropriately adjusting the content of structural units derived from an α-olefin having 2 to 3 carbon atoms in the polymer (b).
[0063] When the ΔH of the polymer (b) is within the above range, the layer (II) has excellent adhesion to the layer (I). ΔH of the polymer (b) is determined by differential scanning calorimetry (DSC measurement) according to JIS K 7122, specifically, calculated from the peak area of a thermogram obtained during a temperature rise of 10° C. / min. More specifically, in order to cancel the thermal history before the measurement, the temperature is raised to 200° C. at 10° C. / min before the measurement, held at that temperature for 3 minutes, then lowered to 0° C. at 10° C. / min, held at that temperature for 3 minutes, and then ΔH is measured.
[0064] The melting point (Tm) of the polymer (b) is preferably less than 120° C., more preferably less than 100° C. It is also preferable that the Tm is not observed. The polymer (b) having a melting point (Tm) within the above range can be obtained, for example, by appropriately adjusting the content of the structural unit derived from an α-olefin having 2 to 3 carbon atoms in the polymer (b).
[0065] When the melting point (Tm) of the polymer (b) is within the above range, the adhesion between the layer (II) and the layer (I) is excellent even when the laminate is produced under low temperature conditions. The melting point (Tm) of the polymer (b) is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section. The weight average molecular weight (Mw) of the polymer (b) measured by gel permeation chromatography (GPC) in terms of standard polystyrene is preferably 1×10 4 More than 1×10 7 Less than or equal to 3×10 4 5×10 or more 6 Less than 5×10, more preferably 4 More than 1×10 6 The molecular weight distribution (ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn)) of the polymer (b) is preferably 1 or more and 3 or less. Details of the method for measuring Mw are described in the Examples section. Mn can also be measured by a similar method.
[0066] When the Mw and Mw / Mn of the polymer (b) are not less than the above lower limit values, the adhesion between the layer (II) and the layer (I) is sufficiently high, and when they are not more than the above upper limit values, it is possible to obtain a polymer (b) that has good solubility in an organic solvent in the adhesive composition (Y) described below and is less likely to solidify or precipitate.
[0067] The olefin-based thermoplastic elastomer is obtained by polymerizing monomers corresponding to the structural units of the polymer to be obtained in the presence of a known solid Ti catalyst or metallocene catalyst that is usually used in the production of olefin-based thermoplastic elastomers. Examples of the metallocene catalyst include catalysts containing a metallocene compound such as rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride, an organoaluminum oxy compound such as methylaluminoxane, and an organoaluminum compound such as triisobutylaluminum. A specific example of a method for producing the olefin-based thermoplastic elastomer is the method described in WO 2004 / 87775.
[0068] The olefin-based thermoplastic elastomer may be a non-graft-modified olefin-based thermoplastic elastomer or a graft-modified olefin-based thermoplastic elastomer (hereinafter also referred to as a "graft-modified olefin-based thermoplastic elastomer"). At least a part or all of the olefin-based thermoplastic elastomer may be a graft-modified olefin-based thermoplastic elastomer (excluding modified olefin-based thermoplastic elastomers graft-modified with a resin containing a structural unit derived from 4-methyl-1-pentene). From the viewpoint of adhesion between the substrate layer (I) and the layer (II), the olefin-based thermoplastic elastomer is preferably a graft-modified olefin-based thermoplastic elastomer.
[0069] The graft-modified olefin-based thermoplastic elastomer can be obtained, for example, by graft-modifying a non-graft-modified olefin-based thermoplastic elastomer with a polar group-containing monomer. The graft-modified olefin-based thermoplastic elastomer is preferably a polymer in which an unmodified polymer (b) is graft-modified with a polar group-containing monomer.
[0070] Examples of the polar group contained in the polar group-containing monomer include a hydroxyl group, an amino group, an epoxy group, a carboxyl group, an acid anhydride group, an ester group, and a thiol group. The polar group-containing monomer may have one type of polar group or two or more types of polar groups. The number of polar groups contained in the polar group-containing monomer may be one or two or more.
[0071] As the polar group-containing monomer, a monomer having an acid anhydride group or a carboxy group is preferred from the viewpoint of being able to improve the adhesion between the layer (II) and the base layer (I). Examples of the polar group-containing monomer include hydroxyl group-containing ethylenically unsaturated compounds, amino group-containing ethylenically unsaturated compounds, epoxy group-containing ethylenically unsaturated compounds, unsaturated carboxylic acids and their anhydrides, vinyl ester compounds, thiol group-containing ethylenically unsaturated compounds, and derivatives thereof.
[0072] Examples of hydroxyl-containing ethylenically unsaturated compounds include hydroxyl-containing (meth)acrylic acid esters such as hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, pentaerythritol mono(meth)acrylate, trimethylolpropane mono(meth)acrylate, and polyethylene glycol mono(meth)acrylate; 10-undecen-1-ol, 1-octen-3-ol, 2-methanol norbornene, hydroxystyrene, N-methylol acrylamide, allyl alcohol, 2-butene-1,4-diol, and glycerin monoalcohol. Note that (meth)acrylate means acrylate and / or methacrylate, and (meth)acrylic acid ester means acrylic acid ester and / or methacrylic acid ester.
[0073] The amino group-containing ethylenically unsaturated compound includes a vinyl monomer having at least one type of amino group or substituted amino group represented by the following formula (1). -NR 1 R 2 Formula (1) In formula (1), R 1 is a hydrogen atom, a methyl group, or an ethyl group, and R2 R is a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cycloalkyl group having 6 to 12 carbon atoms. 2 is preferably a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a cycloalkyl group having 6 to 9 carbon atoms. 2 Examples of the alkyl group include alkyl groups and cycloalkyl groups partially substituted with substituents.
[0074] Examples of such amino group-containing ethylenically unsaturated compounds include amino alkyl ester compounds of acrylic acid or methacrylic acid, vinyl amine compounds, acrylamide compounds or methacrylamide compounds, and imide compounds. Examples of amino alkyl ester compounds of acrylic acid or methacrylic acid include aminomethyl (meth)acrylate, propylaminoethyl (meth)acrylate, dimethylaminoethyl methacrylate, and aminopropyl (meth)acrylate. Examples of vinyl amine compounds include N-vinyl diethylamine and N-acetyl vinylamine. Examples of acrylamide compounds or methacrylamide compounds include acrylamide, methacrylamide, N-methyl acrylamide, and N-methyl methacrylamide. Examples of imide compounds include p-aminohexyl succinimide and 2-aminoethyl succinimide.
[0075] As the epoxy group-containing ethylenically unsaturated compound, a monomer having one or more polymerizable unsaturated bond groups and epoxy groups in one molecule is used. Examples of such epoxy group-containing ethylenically unsaturated compounds include glycidyl esters of unsaturated carboxylic acids, monoglycidyl esters of unsaturated dicarboxylic acids (the alkyl group in the case of monoglycidyl esters has 1 to 12 carbon atoms), alkyl glycidyl esters of p-styrene carboxylic acid, allyl glycidyl ether, 2-methylallyl glycidyl ether, styrene-p-glycidyl ether, and 3,4-epoxy-1-butene. Glycidyl esters of unsaturated carboxylic acids include, for example, glycidyl acrylate and glycidyl methacrylate. Examples of unsaturated dicarboxylic acids include maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (Nadic Acid®), and endo-cis-bicyclo[2,2,1]hept-5-ene-2-methyl-2,3-dicarboxylic acid (Methyl Nadic Acid®).
[0076] Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, and norbornene dicarboxylic acid. Unsaturated carboxylic acid anhydrides include, for example, maleic anhydride, itaconic anhydride, citraconic anhydride, and tetrahydrophthalic anhydride.
[0077] Examples of vinyl ester compounds include vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl isobutyrate, vinyl laurate, vinyl stearate, and vinyl benzoate. Examples of the thiol group-containing ethylenically unsaturated compound include allyl mercaptan, 2-vinylbenzyl mercaptan, 3-vinylbenzyl mercaptan, 4-vinylbenzyl mercaptan, and vinylthiophenol.
[0078] Derivatives of the above compounds include, for example, unsaturated carboxylic acid derivatives other than unsaturated carboxylic acid anhydrides, such as malenyl chloride, malenylimide, dimethyl maleate, monomethyl maleate, diethyl maleate, diethyl fumarate, and dimethyl itaconate.
[0079] As the polar group-containing monomer, from the viewpoint of improving the adhesion between the layer (II) and the base layer (I), unsaturated carboxylic acids and unsaturated carboxylic anhydrides are preferred, unsaturated carboxylic anhydrides are more preferred, and maleic anhydride is even more preferred. The polar group-containing monomer may be used alone or in combination of two or more kinds.
[0080] The content (modification amount) of structural units derived from polar group-containing monomers in the graft-modified olefin-based thermoplastic elastomer is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and preferably 15 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, still more preferably 4 mass% or less, and particularly preferably 2 mass% or less, based on 100 mass% of all structural units in the graft-modified olefin-based thermoplastic elastomer. The graft modification amount means the mass of the constituent units derived from the polar group-containing monomer used for the graft modification relative to the mass of the graft-modified olefinic thermoplastic elastomer.
[0081] The amount of graft modification in the olefinic thermoplastic elastomer can be adjusted, for example, by the charge ratio when the unmodified olefinic thermoplastic elastomer and the polar group-containing monomer are reacted in the presence of a radical initiator or the like.
[0082] The amount of graft modification is measured by infrared spectroscopy (IR), and can be calculated, for example, by performing IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (FT-IR410, manufactured by JASCO Corporation). When it is difficult to measure the amount of graft modification by infrared spectroscopy (IR), the amount of graft modification can be calculated by 1 It may also be measured by H-NMR. When maleic anhydride is used as the polar group-containing monomer, the IR spectrophotometer is used to measure the peak wavelength at 1790 cm -1 The amount of grafting may be determined based on the absorption of the carbonyl group of maleic anhydride detected nearby.
[0083] The ΔH of the graft-modified olefin-based thermoplastic elastomer is preferably 0 to 40 J / g. The ΔH of the graft-modified olefin-based thermoplastic elastomer is preferably 0 J / g or more, more preferably 3 J / g or more, even more preferably 5 J / g or more, and is preferably 40 J / g or less, more preferably 35 J / g or less, even more preferably 30 J / g or less. It is also preferable that ΔH is 0 J / g. The ΔH of the graft-modified olefin-based thermoplastic elastomer is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section.
[0084] When the ΔH of the graft-modified olefin-based thermoplastic elastomer is equal to or less than the above upper limit, the adhesion between the layer (II) and the layer (I) is excellent. A graft-modified olefin-based thermoplastic elastomer having a ΔH within the above range can be obtained, for example, by appropriately adjusting the content of structural units derived from an α-olefin having 2 to 3 carbon atoms in the graft-modified olefin-based thermoplastic elastomer.
[0085] The melting point (Tm) of the graft-modified olefin-based thermoplastic elastomer is preferably 40° C. or more and less than 120° C. The melting point (Tm) of the graft-modified olefin-based thermoplastic elastomer is preferably less than 120° C., more preferably less than 100° C., even more preferably 90° C. or less, particularly preferably 80° C. or less, and is preferably 40° C. or more, more preferably 50° C. or more. It is also preferable that the melting point (Tm) is not observed. The melting point (Tm) of the graft-modified olefin-based thermoplastic elastomer is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section.
[0086] When the melting point (Tm) of the graft-modified olefin thermoplastic elastomer is within the above range, the adhesion between the layer (II) and the layer (I) is excellent even when the laminate is produced at a low temperature. A graft-modified olefin-based thermoplastic elastomer having a melting point (Tm) within the above range can be obtained, for example, by appropriately adjusting the content of structural units derived from an α-olefin having 2 to 3 carbon atoms in the graft-modified olefin-based thermoplastic elastomer.
[0087] The weight average molecular weight (Mw) of the graft-modified olefin thermoplastic elastomer measured by GPC in terms of standard polystyrene is preferably 1×10 4 More than 1×10 7 The Mw of the graft-modified olefin-based thermoplastic elastomer in terms of standard polystyrene is preferably 1×10 4 More preferably, 2×10 4 More preferably, 3×10 4 More preferably, 1×10 7 Less than or equal to 5×10 6 Less than 1×10, more preferably 6 The following is the result. The details of the method for measuring Mw are described in the Examples section.
[0088] When the Mw of the graft-modified olefin-based thermoplastic elastomer is equal to or greater than the above lower limit, the adhesion between the layer (II) and the layer (I) is excellent, and when it is equal to or less than the above upper limit, the graft-modified olefin-based thermoplastic elastomer has good solubility in organic solvents in the adhesive composition (Y) described below and is less likely to solidify or precipitate.
[0089] The Mw / Mn of the graft-modified olefin-based thermoplastic elastomer is preferably 1 to 3. The Mw / Mn of the graft-modified olefin-based thermoplastic elastomer is preferably 1 or more, more preferably 1.5 or more, and preferably 3 or less, more preferably 2.5 or less. When the Mw / Mn of the graft-modified olefin-based thermoplastic elastomer is at least the above lower limit, the solubility in organic solvents in the adhesive composition (Y) is good, and a graft-modified olefin-based thermoplastic elastomer that is less likely to solidify or precipitate can be obtained. When the Mw / Mn is no greater than the above upper limit, the adhesion between the layer (II) and the layer (I) is excellent.
[0090] The kinetic viscosity of the graft-modified olefin thermoplastic elastomer at 40° C. is preferably more than 500,000 cSt. If the kinetic viscosity exceeds 500,000 cSt, the fluidity may be so low that the kinetic viscosity cannot be measured.
[0091] An example of a method for graft copolymerizing a polar group-containing monomer onto an unmodified olefin-based thermoplastic elastomer is a method in which the unmodified olefin-based thermoplastic elastomer is dissolved in an organic solvent, and the polar group-containing monomer and a radical polymerization initiator are added, followed by heating and stirring to carry out the graft copolymerization reaction.
[0092] Examples of the radical polymerization initiator include organic peroxides, organic peresters, and azo compounds. Specific examples of the radical polymerization initiator include organic peroxides such as benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)hexyne-3, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, and tert-butylperoxydiethyl acetate; and azo compounds such as azobis-isobutyltolyl and dimethylazoisobutylnitrile. The amount of the radical polymerization initiator is preferably about 0.001 to 10 parts by mass based on 100 parts by mass of the unmodified olefin-based thermoplastic elastomer.
[0093] Examples of the olefin-based polymer (B) other than the olefin-based thermoplastic elastomer include hydrocarbon-based synthetic oils. When the olefin-based polymer (B) contains a hydrocarbon-based synthetic oil, the adhesion between the layer (I) and the layer (II) is excellent.
[0094] The synthetic hydrocarbon oils may be used alone or in combination of two or more. Examples of the hydrocarbon synthetic oil include polymers of α-olefins having 2 to 20 carbon atoms. Among them, oligomers obtained by homopolymerizing α-olefins having 2 to 20 carbon atoms and oligomers obtained by copolymerizing two or more of these α-olefins are preferred.
[0095] Examples of the α-olefin having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-octene, 1-decene, and 1-dodecene. The hydrocarbon synthetic oil is preferably an ethylene-based copolymer containing structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms. The content of the structural units derived from ethylene in the ethylene-based copolymer is preferably 30 mol% or more, more preferably 40 mol% or more, and preferably 70 mol% or less, more preferably 60 mol% or less, relative to 100 mol% in total of the structural units derived from ethylene and the structural units derived from an α-olefin having 3 to 20 carbon atoms.
[0096] The kinematic viscosity of the synthetic hydrocarbon oil at 40° C. is preferably 30 to 500,000 cSt. The kinematic viscosity of the synthetic hydrocarbon oil at 40° C. is preferably 30 cSt or more, more preferably 300 cSt or more, even more preferably 5,000 cSt or more, and preferably 500,000 cSt or less, more preferably 400,000 cSt or less, even more preferably 300,000 cSt or less.
[0097] The kinetic viscosity of the synthetic hydrocarbon oil at 200° C. is preferably 10 to 100,000 cSt. The kinetic viscosity of the synthetic hydrocarbon oil at 200° C. is preferably 10 cSt or more, more preferably 20 cSt or more, even more preferably 30 cSt or more, and is preferably 100,000 cSt or less, more preferably 80,000 cSt or less, even more preferably 60,000 cSt or less. The kinematic viscosity of the synthetic hydrocarbon oil at 40°C and 200°C can be measured based on ASTM D 445.
[0098] When the kinetic viscosity of the synthetic hydrocarbon oil at 40° C. or 200° C. is within the above range, the layer (II) containing the synthetic hydrocarbon oil has excellent adhesion to the layer (I).
[0099] When the olefin polymer (B) contains an olefin thermoplastic elastomer and a hydrocarbon synthetic oil, the adhesion between the layer (I) and the layer (II) is excellent. When the olefin polymer (B) contains an olefin thermoplastic elastomer and a hydrocarbon synthetic oil, the content of the hydrocarbon synthetic oil is preferably 1 part by mass or more and 80 parts by mass or less, more preferably 2 parts by mass or more and 70 parts by mass or less, and preferably 3 parts by mass or more and 60 parts by mass or less, per 100 parts by mass of the olefin thermoplastic elastomer, from the viewpoint of adhesion between Layer (I) and Layer (II).
[0100] The olefin polymer (B) may contain only an olefin thermoplastic elastomer, or may contain an olefin thermoplastic elastomer and a hydrocarbon synthetic oil. The olefin polymer (B) may be one type alone or two or more types.
[0101] <Other ingredients> The layer (II) may contain other components as necessary, such as antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, leveling agents, reinforcing agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, and fillers.
[0102] When the layer (II) contains other components, the total content of the other components in the layer (II) is preferably 0.005 to 5 mass %, more preferably 0.01 to 3 mass %, based on 100 mass % of the layer (II).
[0103] [Laminate] The laminate of the present disclosure includes a substrate layer (I) and a layer (II). The laminate may include only the base layer (I) and the layer (II), or may include layers other than the base layer (I) and the layer (II). The layer (II) contained in the laminate may be one layer or two or more layers. When the laminate contains two or more layers (II), the two or more layers (II) may be the same or different from each other.
[0104] The laminate may include a layer (II) on only one side of the substrate layer (I), or may include layers (II) on both sides of the substrate layer (I). For example, the laminate may include a substrate layer (I) and a layer (II) provided on one side of the substrate layer (I), or may include a first layer (II), a substrate layer (I), and a second layer (II) in this order in the stacking direction.
[0105] In one embodiment, the laminate of the present disclosure preferably includes a layer (II) constituting one of the outermost layers, or preferably includes a first layer (II) constituting one of the outermost layers and a second layer (II) constituting the other outermost layer. Such a laminate is preferably used as a release film as described later.
[0106] Figures 1 and 2 show cross-sectional views of a laminate according to one embodiment. The laminate 1 shown in Figure 1 includes a base layer (I) 10 and a layer (II) 20. The laminate 1 shown in Figure 2 includes a first layer (II) 20A, a base layer (I) 10, and a second layer (II) 20B.
[0107] The thickness of the laminate of the present disclosure is preferably 10 to 600 μm, more preferably 20 to 500 μm, even more preferably 30 to 400 μm, still more preferably 40 to 300 μm, and particularly preferably 50 to 200 μm. The thickness of the laminate is measured, for example, by observing the cross section of the laminate in a direction perpendicular to the surface of the laminate with a scanning electron microscope (SEM).
[0108] The laminate of the present disclosure may further include layers other than the substrate layer (I) and the layer (II). The laminate may further include a primer layer, for example, between the substrate layer (I) and the layer (II). The primer layer is provided, for example, to improve the adhesion between the substrate layer (I) and the layer (II). The primer layer is provided, for example, on the surface of the substrate layer (I).
[0109] The laminate can be obtained, for example, by forming a layer (II) on the surface of a substrate film corresponding to the substrate layer (I). A method for producing the laminate includes, for example, a step (1) of preparing a composition containing a polymer (A) and an olefin polymer (B), a step (2) of applying the composition to at least one surface of a substrate film corresponding to the substrate layer (I), and a step (3) of aging the substrate film to which the composition has been applied.
[0110] In step (1), the composition containing the polymer (A) and the olefin-based polymer (B) may be prepared, for example, by mixing a composition (X) containing the polymer (A) and a solvent with an adhesive composition (Y) containing the olefin-based polymer (B) and a solvent.
[0111] In one embodiment, the composition (X) may be a liquid in which the polymer (A) is dissolved or dispersed in a solvent. In one embodiment, the adhesive composition (Y) may be a liquid in which the olefin polymer (B) is dissolved or dispersed in a solvent. The composition (X) may further contain other components that may be contained in the layer (II) described above. The adhesive composition (Y) may further contain other components that may be contained in the layer (II) described above.
[0112] The solvent in the composition (X) may be any solvent capable of dissolving or dispersing the polymer (A), and is preferably an organic solvent. The solvent in the adhesive composition (Y) may be any solvent capable of dissolving or dispersing the olefin polymer (B), and is preferably an organic solvent. Examples of organic solvents include aliphatic hydrocarbons such as n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, and decahydronaphthalene; aromatic hydrocarbons such as benzene, toluene, and xylene; alcohols such as methanol, ethanol, isopropyl alcohol, butanol, and hexanol; ketone solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, and acetophenone; cellosolves such as methyl cellosolve and ethyl cellosolve; esters such as methyl acetate, ethyl acetate, butyl acetate, and butyl formate; halogenated hydrocarbons such as trichloroethylene, dichloroethylene, and chlorobenzene; normal paraffin solvents and isoparaffin solvents.
[0113] The solvent in composition (X) is preferably toluene, cyclohexane, methylcyclohexane and ethyl acetate.
[0114] From the viewpoint of the solubility or dispersibility of the olefin-based thermoplastic elastomer, the solvent in the adhesive composition (Y) is preferably an aromatic hydrocarbon, a normal paraffin-based solvent, an isoparaffin-based solvent, an alicyclic hydrocarbon, an alicyclic hydrocarbon / ester mixed solvent, or an alicyclic hydrocarbon / ketone solvent mixed solvent, and more preferably toluene, a methylcyclohexane / ethyl acetate mixed solvent, or a methylcyclohexane / methyl ethyl ketone mixed solvent. The organic solvent may be used alone or in combination of two or more kinds.
[0115] The organic solvent in the adhesive composition (Y) may be the same as or different from the organic solvent in the composition (X). When the organic solvent in the adhesive composition (Y) and the organic solvent in the composition (X) are the same or have similar boiling points, the removal of the solvent in the step (2) is easy.
[0116] The solvent may be one type or two or more types.
[0117] The solid content of composition (X) is preferably 0.1 to 50 mass%, more preferably 1 to 30 mass%, and further preferably 2 to 10 mass%. In this specification, the solid content of composition (X) refers to all components excluding the solvent. When the content of the solid content in the composition (X) is within the above range, a good balance is achieved between the handleability of the composition (X) and the ease of removing the solvent from the composition (X) when forming the layer (II).
[0118] The content of the solvent in the composition (X) is preferably from 50 to 99.9% by mass, more preferably from 70 to 99% by mass, and further preferably from 90 to 98% by mass.
[0119] The solid content of the adhesive composition (Y) is preferably 5 to 40 mass%, more preferably 10 to 30 mass%, and further preferably 15 to 25 mass%, from the viewpoint of dissolving the olefin polymer (B) in the organic solvent. In the present disclosure, the solid content of the adhesive composition (Y) refers to all components excluding the solvent. The content of the solvent in the adhesive composition (Y) is preferably 60 to 95 mass %, more preferably 70 to 90 mass %, and even more preferably 75 to 85 mass %. The composition comprising the composition (X) and the adhesive composition (Y), each having a solvent content within the above range, is easily applied in step (2).
[0120] The composition (X) can be produced, for example, by mixing the polymer (A), a solvent, and, if desired, other components.
[0121] When the olefin-based thermoplastic elastomer is a non-graft-modified olefin-based thermoplastic elastomer, the adhesive composition (Y) can be prepared by dispersing the non-graft-modified olefin-based thermoplastic elastomer in a solvent. When at least a part of the olefin-based thermoplastic elastomer is a graft-modified olefin-based thermoplastic elastomer, the adhesive composition (Y) can be prepared as follows.
[0122] As described above, the grafting reaction can be carried out in an organic solvent or without a solvent. When the reaction is carried out in an organic solvent, the adhesive composition (Y) can be prepared as is or with the addition of the same or a different type of organic solvent. When the graft reaction is carried out without using an organic solvent, the adhesive composition (Y) can be prepared by adding an organic solvent again. When the olefin-based thermoplastic elastomer is a mixture of a graft-modified olefin-based thermoplastic elastomer and a non-graft-modified olefin-based thermoplastic elastomer, the adhesive composition (Y) may be prepared by mixing a previously prepared mixture with an organic solvent, or the adhesive composition (Y) may be prepared by adding the graft-modified olefin-based thermoplastic elastomer and the non-graft-modified olefin-based thermoplastic elastomer to the organic solvent, respectively.
[0123] An example of step (2) will be described. In this example, a coating agent that is one embodiment of a composition containing a polymer (A) and an olefin-based polymer (B) is used. In step (2), specifically, a composition containing a polymer (A) and an olefin-based polymer (B) is applied to at least one surface of a substrate film that corresponds to the substrate layer (I). When the composition contains a solvent, the solvent in the composition is removed to a certain extent by, for example, heating to a temperature close to the boiling point of the solvent that is most abundant in the composition.
[0124] The application in step (2) can be carried out by a conventionally known method, and examples of the method that can be used include application using an applicator, application using a brush or paintbrush, spraying, screen printing, flow coating, spin coating, dipping, a bar coater, a T-die, a T-die with a bar, a doctor knife, roll coating, and die coating.
[0125] The removal of the solvent in step (2) does not only mean the complete removal of the solvent from the composition containing the polymer (A) and the olefin polymer (B), but also includes the removal of the solvent to an extent that a layer can be formed. Specifically, the removal of the solvent includes the removal of the solvent until the total content of the solvent becomes about 0.001 to 0.5 mass% relative to 100% mass of the layer (II).
[0126] The method for removing the solvent in step (2) is not particularly limited, and the solvent may be dried by leaving it to stand, but is generally removed by heating and drying at 30 to 220°C. In order to prevent thermal deterioration or thermal decomposition of the polymer (A), it is preferable to remove the solvent at a temperature lower than the melting point (Tm) of the polymer (A). The amount of solvent remaining in the layer (II) after drying is preferably 0.5 mass% or less in total, more preferably 0.05 mass% or less in total, and even more preferably 0.01 mass% or less in total, based on 100% mass of the layer (II).
[0127] The aging treatment of the base film in step (3) can be carried out by leaving it at room temperature, but is preferably carried out in an oven or the like. The aging temperature is preferably less than 80° C., more preferably less than 70° C., further preferably less than 60° C., and particularly preferably less than 50° C. The aging temperature is preferably 10° C. or higher. The aging time varies depending on the temperature conditions, but is preferably from 1 hour to 72 hours, more preferably from 2 hours to 50 hours, even more preferably from 3 hours to 40 hours, and particularly preferably from 3 hours to 30 hours. The aging treatment improves the adhesion between the substrate layer (I) and the layer (II).
[0128] <Applications of laminates> The laminate of the present disclosure can be suitably used as a release film. Examples of the release film include a release film used in the manufacturing process of an optical component, a release film used in the manufacturing process of a thin-film ceramic capacitor, a separator for tapes and other adhesives, a separator for adhesives and resin sheet film formation, or a separator for architectural window films. Examples of optical components include a light guide plate, a polarizing film, a light diffusion film, a retardation film, and an anti-reflection film.
[0129] Since the laminate of the present disclosure has excellent heat resistance as described above, it can be suitably used as a protective film for, for example, a display device, a semiconductor device, an optical member, a printed circuit board, a capacitor, etc.
[0130] [Example of the situation] The present disclosure relates to, for example, the following [1] to
[12] . [1] A substrate layer (I); A layer (II) including a 4-methyl-1-pentene polymer (A) satisfying the following requirements (a) to (c), and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A); A laminate comprising: (a) a melting point (Tm) measured by differential scanning calorimetry (DSC) of greater than 180°C and less than or equal to 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230°C or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by differential scanning calorimetry (DSC) is 210°C or lower.
[0131] [2] The laminate according to [1], wherein the base layer (I) contains a polyolefin having a melting point (Tm) measured by a differential scanning calorimeter (DSC) of 200° C. or lower.
[0132] [3] The laminate according to [2], wherein the polyolefin in the base layer (I) having a melting point (Tm) of 200° C. or lower includes at least one selected from the group consisting of polypropylene and polyethylene.
[0133] [4] The laminate according to any one of [1] to [3], wherein the layer (II) has a surface free energy of 32 mN / m or less on a surface opposite to the surface facing the base layer (I).
[0134] [5] The laminate according to any one of [1] to [4], wherein the olefin polymer (B) contains an olefin thermoplastic elastomer.
[0135] [6] The laminate according to any one of [1] to [5], wherein the layer (II) contains 100 to 4,000 parts by mass of the olefin polymer (B) based on 100 parts by mass of the 4-methyl-1-pentene polymer (A).
[0136] [7] The laminate according to [5] or [6], wherein a part or all of the olefin-based thermoplastic elastomer is a graft-modified olefin-based thermoplastic elastomer graft-modified with a polar group-containing monomer.
[0137] [8] The laminate according to any one of [1] to [7], wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. of 0.5 to 5.0 dl / g.
[0138] [9] The 4-methyl-1-pentene polymer (A) contains a structural unit (i) derived from 4-methyl-1-pentene, and, if desired, a structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), In the 4-methyl-1-pentene polymer (A), The content (U1) of the structural unit (i) is 84 to 100 mol %, The content (U2) of the structural unit (ii) is 0 to 16 mol % (wherein the total of U1 and U2 is 100 mol %); The laminate according to any one of [1] to [8].
[0139]
[10] The laminate according to [9], wherein the structural unit (ii) is a structural unit derived from an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).
[0140]
[11] The laminate according to any one of [2] to
[10] , wherein the polyolefin in the base layer (I) having a melting point (Tm) of 200° C. or lower contains polypropylene.
[0141]
[12] A step of preparing a base film and a composition containing a 4-methyl-1-pentene polymer (A) and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A), which satisfy the following requirements (a) to (c): applying the composition to a surface of the substrate film; Aging the substrate film coated with the composition in an environment of less than 80° C. for 72 hours or less; A method for producing a laminate, comprising: (a) a melting point (Tm) measured by differential scanning calorimetry (DSC) of greater than 180°C and less than or equal to 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230°C or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by differential scanning calorimetry (DSC) is 210°C or lower. EXAMPLES
[0142] The laminate of the present disclosure will be described in more detail below with reference to examples, although the laminate of the present disclosure is not limited to these examples.
[0143] <Method of measuring physical properties of polymer> [composition] The content (U1) of the structural unit (structural unit (i)) derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) and the content (U2) of the structural unit (structural unit (ii)) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) are obtained by the following apparatus and under the following conditions: 13 Calculated from C-NMR spectrum.
[0144] A nuclear magnetic resonance spectrometer, ECP500, manufactured by JEOL Ltd., was used. Solvent: o-dichlorobenzene / heavy benzene (80% by volume / 20% by volume) mixed solvent. Sample concentration: 55 mg / 0.6 mL. Measurement temperature: 120°C. Observation nuclei: 13 The measurements were performed under the following conditions: C (125 MHz), sequence: single pulse proton decoupling, pulse width: 4.7 μsec (45° pulse), repetition time: 5.5 sec, number of integrations: 10,000 or more, chemical shift reference value: 27.50 ppm. 13 U1 and U2 were quantified by C-NMR spectroscopy. The olefin polymer (B) can be obtained under the same conditions using the same apparatus. 13 The content of each structural unit was quantified from the C-NMR spectrum.
[0145] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. That is, about 20 mg of the 4-methyl-1-pentene polymer (A) was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η spThe decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0)
[0146] [Graft modification amount] The amount of graft modification of the graft-modified 4-methyl-1-pentene polymer, i.e., the content of the constitutional units derived from the ethylenically unsaturated monomer used for the graft modification when the mass of the graft-modified 4-methyl-1-pentene polymer is taken as 100 mass%, was determined by the following method. First, the graft-modified 4-methyl-1-pentene polymer was treated at 250° C. for 5 minutes with preheating and pressing for 3 minutes to prepare a pressed film, and the pressed film was subjected to IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (manufactured by JASCO Corporation, FT-IR410 model). In the following production example, maleic anhydride was used for the graft modification, so that the peak at 1860 cm -1 and 4321 cm -1 The amount of graft modification was calculated from the peak intensity. The amount of graft modification of the graft-modified olefin-based thermoplastic elastomer (B1) was measured by IR measurement in the same manner as above, and the graft modification amount was measured at 1790 cm -1 The intensity of the neighboring peaks was used for calculation.
[0147] [Melting point (Tm), endothermic end temperature (TmE), exothermic onset temperature (TcS) and crystallization temperature (Tc) of 4-methyl-1-pentene polymer (A)] Using a differential scanning calorimeter (DSC) measuring device (model: DSC220C) manufactured by Seiko Instruments Inc., an exothermic-endothermic curve was obtained in accordance with ASTM D 3418, and the melting point (Tm) and crystallization temperature (Tc) were determined as follows. About 5 mg of a sample of 4-methyl-1-pentene polymer (A) was placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled to 20°C at a cooling rate of 10°C / min to obtain a crystallization (exothermic) curve. After holding at 20°C for 5 minutes, the sample was again heated from 20°C to 280°C at a heating rate of 10°C / min to obtain a melting (endothermic) curve.
[0148] The temperature at the apex of the crystallization peak that appeared during the first cooling run was taken as the crystallization temperature (Tc). If multiple crystallization peaks were detected, the one with the maximum temperature was taken as the crystallization temperature (Tc). The temperature at the apex of the melting peak that appeared during the second heating run was taken as the melting point (Tm). If multiple melting peaks were detected, the one with the maximum temperature was taken as the melting point (Tm).
[0149] The temperature at which the endotherm of the melting (endotherm) curve ended was taken as the endotherm end temperature (TmE), and the temperature at which the heat generation began of the crystallization (exotherm) curve was taken as the exotherm start temperature (TcS). The temperature at which endotherm ends is the temperature at which it can be confirmed that the melting (endotherm) curve near the end of endotherm begins to deviate from the baseline on the high temperature side of the melting peak, resulting in a difference in the amount of heat. The temperature at which heat generation begins is the temperature at which it can be confirmed that the crystallization (exotherm) curve near the start of exotherm begins to deviate from the baseline on the high temperature side of the crystallization peak, resulting in a difference in the amount of heat.
[0150] [Melting point and heat of fusion of olefin-based thermoplastic elastomer and graft-modified olefin-based thermoplastic elastomer (B1)] The melting point and heat of fusion were determined using a differential scanning calorimeter (TA Instruments; DSC-Q1000). After heating from 30°C to 200°C at 10°C / min, the sample was held at 200°C for 3 minutes, cooled to 0°C at 10°C / min, and then heated again to 200°C at 10°C / min. In this process, the melting point and heat of fusion were determined according to JIS K 7122 from the thermogram obtained during the second heating step.
[0151] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) of the olefin polymer (B) was measured by gel permeation chromatography (Shimadzu Corporation; LC-10 series) under the following conditions. Detector: Shimadzu Corporation; C-R4A Column: TSKG 6000H-TSKG 4000H-TSKG 3000H-TSKG 2000H (Tosoh Corporation) Mobile phase: Tetrahydrofuran ·Temperature: 40℃ ·Flow rate: 0.8ml / min The Mw was calculated using a calibration curve prepared from monodisperse standard polystyrene.
[0152] [Measurement of dynamic viscosity] Based on ASTM D 445, the kinematic viscosities of the hydrocarbon-based synthetic oil (B2) at 40°C and 200°C were determined.
[0153] <Preparation of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride> Using the method described in Preliminary Experiment 5 (paragraphs
[0346] to
[0348] ) of WO 2014 / 123212, (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride was synthesized.
[0154] <Production Example 1: Production of Polymer 1> 500 mL of 4-methyl-1-pentene and 220 mL of heptane were charged into a 1.5 L SUS autoclave equipped with an agitator, which had been thoroughly purged with nitrogen, at 23°C. 30 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C.
[0155] Thereafter, 2 mL of a toluene solution containing 0.039 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.00013 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained above was injected into the autoclave under pressure with nitrogen to initiate polymerization.
[0156] During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 10 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 1. The obtained polymer 1 was dried at 130°C under reduced pressure for 10 hours. Various physical properties of polymer 1 are shown in Table 1.
[0157] <Production Example 2: Production of Polymer 2> [Synthesis Example 2-1: Production of olefin polymerization catalyst] In a 200 mL three-neck flask equipped with a stirrer and thoroughly purged with nitrogen, 30 mL of purified decane and 14.65 mmol, in terms of aluminum atoms, of particulate solid polymethylaluminoxane having a D50 of 28 μm and an aluminum atom content of 43 mass% (synthesized using the method described in WO 2014 / 123212) were charged at 30° C. under a nitrogen stream to obtain a suspension.
[0158] To the suspension, 50.0 mg (0.0586 mmol) of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained above was added as a 4.58 mmol / L toluene solution with stirring. After 1 hour, stirring was stopped and the resulting mixture was washed with 100 mL of decane by decantation, and then decane was added to obtain 50 mL of a slurry liquid. The zirconium atom loading rate of the slurry liquid was 98%.
[0159] [Synthesis Example 2-2: Preparation of prepolymerization catalyst component] To the slurry liquid prepared in Synthesis Example 2-1, 1.0 mL of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atom) was added under a nitrogen stream at 25°C, and after cooling to 15°C, 10 mL of 4-methyl-1-pentene was added to the reactor over 60 minutes. The start of the addition of 4-methyl-1-pentene was taken as the start of prepolymerization. Stirring was stopped 2.0 hours after the start of prepolymerization, and the resulting mixture was washed three times with 100 mL of decane by decantation. The prepolymerization catalyst component was a decane slurry (9.5 g / L, 0.56 mmol / L in terms of zirconium atom).
[0160] [Preparation of polymer 2a] At room temperature under a nitrogen stream, 425 mL of purified decane was placed in a 1 L stainless steel polymerization vessel equipped with a stirrer, and the temperature was raised to 40° C. After the temperature reached 40° C., 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol in terms of zirconium atoms of the decane slurry of the prepolymerized catalyst component of Synthesis Example 2-2 was charged. Further, 23.75 NmL of hydrogen was charged, and then a mixture of 230 mL of 4-methyl-1-pentene and 22.4 mL of a mixture of 1-hexadecene and 1-octadecene (Linearene 168, manufactured by Idemitsu Kosan Co., Ltd.) was continuously charged into the polymerization vessel at a constant rate over 2 hours.
[0161] The start of the addition of the mixed liquid was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was added 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain polymer 2a (yield: 142 g). The content (U1) of the structural unit (i) in the polymer 2a was 96.5 mol%, and the content (U2) of the structural unit (ii) in the polymer 2a was 3.5 mol%. The melting point (Tm) of the polymer 2a was 201° C., and the intrinsic viscosity [η] was 1.0 dl / g.
[0162] [Production of Polymer 2] Polymer 2a was mixed with 0.02 phr of the phenolic stabilizer Irganox1010 (manufactured by BASF Chiba) as a heat stabilizer, and the mixture was kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain Polymer 2. Various physical properties of the obtained Polymer 2 are shown in Table 1. The content (U1) of the structural unit (i) and the content (U2) of the structural unit (ii) in polymer 2 were the same as those in polymer 2a.
[0163] <Production Example 3: Production of Polymer 3> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 20 mL of a mixture of 1-hexadecene and 1-octadecene (Linearene 168, manufactured by Idemitsu Kosan Co., Ltd.) and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C.
[0164] Thereafter, 2 mL of a toluene solution containing 0.033 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.00011 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained above was injected into the autoclave under nitrogen pressure to initiate polymerization.
[0165] During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 13 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 3. The obtained polymer 3 was dried at 130°C under reduced pressure for 10 hours. Various physical properties of polymer 3 are shown in Table 1.
[0166] <Production Example 4: Production of Polymer 4> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 15 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C.
[0167] Thereafter, 2 mL of a toluene solution containing 0.06 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.0002 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained above was injected into the autoclave under nitrogen pressure to initiate polymerization.
[0168] During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 30 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 4. The obtained polymer 4 was dried at 130°C under reduced pressure for 10 hours. Various physical properties of the obtained polymer 4 are shown in Table 1.
[0169] <Production Example 5: Production of Polymer 5> Polymer 5 was obtained by blending 100 parts by mass of polymer 2, 2 parts by mass of maleic anhydride, and 0.02 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (Perhexyne 25B, manufactured by NOF Corporation) as an organic peroxide in a ratio of 1:1, and kneading the mixture in a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm.
[0170] U1 and U2 in polymer 5 were the same as those in polymer 2. Polymer 5 had a melting point (Tm) of 201° C., a limiting viscosity [η] of 1.0 dl / g, and a graft amount of 1.5 mass%. Other physical properties of polymer 5 are shown in Table 1.
[0171] [Table 1]
[0172] <<Preparation of composition (X)>> <Preparation of composition (X1)> To 100 parts by mass of polymer 1, 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration became 5% by mass. The mixture was stirred at 200 rpm at 90°C for 1 hour to prepare a composition (X1) containing polymer 1.
[0173] <Preparation of composition (X2)> Composition (X2) was prepared in the same manner as in the preparation of composition (X1), except that polymer 2 was used instead of polymer 1.
[0174] <Preparation of composition (X3)> Composition (X3) was prepared in the same manner as in the preparation of composition (X1), except that polymer 3 was used instead of polymer 1.
[0175] <Preparation of composition (X4)> Composition (X4) was prepared in the same manner as in the preparation of composition (X1), except that polymer 4 was used instead of polymer 1.
[0176] <Preparation of composition (X5)> To 100 parts by mass of polymer 5, 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 6.25% by mass, and the mixture was stirred at 200 rpm at 90 ° C. for 3 hours. Thereafter, ethyl acetate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 5% by mass, and the mixture was stirred at 200 rpm for 15 minutes at 60 ° C. to prepare a composition (X5) containing polymer 5.
[0177] <Preparation of composition (X6)> After the temperature of the composition (X5) was lowered to 23°C, 0.03 parts by mass (wherein the amount of polymer 5 in the composition (X5) is 100 parts by mass) of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) was added and the mixture was stirred at 200 rpm for 5 minutes to prepare a composition (X6) containing polymer 5 and an isocyanate compound.
[0178] <<Production of Adhesive Composition (Y1)>> <Synthesis of Graft Modified Olefin Thermoplastic Elastomer (B1)> In a 2L autoclave that had been thoroughly purged with nitrogen, 900mL of hexane and 90g of 1-butene were charged, 1mmol of triisobutylaluminum was added, and the temperature was raised to 70°C. Then, propylene was fed in to reduce the total pressure to 7kg / cm. 2 G, 0.30 mmol of methylaluminoxane and 0.001 mmol of rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride (calculated as Zr atom) were added, and propylene was continuously fed to maintain the total pressure at 7 kg / cm 2 Polymerization was carried out for 30 minutes while maintaining the temperature at G. After polymerization, the polymer was degassed and recovered in a large amount of methanol, and dried under reduced pressure at 110° C. for 12 hours. The melting point of the obtained propylene-1-butene copolymer was 78.3°C, the heat of fusion was 29.2 J / g, the Mw was 330,000, the content of structural units derived from propylene was 67.2 mol%, and the content of structural units derived from 1-butene was 32.8 mol%.
[0179] 3 kg of the above propylene-1-butene copolymer was added to 10 L of toluene, and the mixture was heated to 145°C under a nitrogen atmosphere to dissolve in toluene. 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide were then added to the system over 4 hours while stirring, and the mixture was stirred at 145°C for 2 hours. After cooling, a large amount of acetone was added to precipitate the modified propylene-1-butene copolymer, which was then filtered, washed with acetone, and vacuum dried. The melting point of the obtained maleic anhydride-modified propylene-1-butene copolymer (graft-modified olefin-based thermoplastic elastomer (B1)) was 75.8°C, the heat of fusion was 28.6 J / g, the Mw was 110,000, and the amount of maleic anhydride modification (the content of structural units derived from maleic anhydride) was 1 mass%.
[0180] <Synthesis of synthetic hydrocarbon oil (B2)> In a continuous polymerization reactor equipped with an agitator and thoroughly purifying with nitrogen, 1 L of dehydrated and purified hexane was added, and ethylaluminum sesquichloride (Al(C)) adjusted to 96 mmol / L was added. 2 H 5 ) 1.5 ·Cl1.5 After continuously feeding a hexane solution of VO(OC) at a rate of 500 mL / h for 1 hour, VO(OC) was added as a catalyst at a concentration of 16 mmol / L. 2 H 5 ) C l2 The hexane solution of 500mL / h and hexane were continuously fed at 500mL / h. Meanwhile, the polymerization liquid was continuously withdrawn from the top of the polymerization vessel so that the polymerization liquid in the polymerization vessel was always 1L. Next, ethylene gas was fed at 47L / h, propylene gas at 47L / h, and hydrogen gas at 20L / h using a bubbling tube. The copolymerization reaction was carried out at 35°C by circulating a coolant through a jacket attached to the outside of the polymerization vessel. The obtained polymerization solution was deashed with hydrochloric acid, then poured into a large amount of methanol to precipitate an ethylene-propylene copolymer, and dried under reduced pressure at 130°C for 24 hours. The resulting ethylene-propylene copolymer (hydrocarbon-based synthetic oil (B2)) had an ethylene-derived structural unit content of 55.9 mol%, a propylene-derived structural unit content of 44.1 mol%, an Mw of 14,000, a kinetic viscosity at 40°C of 37,500 cSt, and a kinetic viscosity at 200°C of 132 cSt.
[0181] 16 parts by mass of the graft-modified olefin-based thermoplastic elastomer (B1) and 4 parts by mass of the carbon-based synthetic oil (B2) were heated and dissolved in 80 parts by mass of a mixed solvent of methylcyclohexane / ethyl acetate = 8 / 2 (mass ratio) to prepare 100 parts by mass of an adhesive composition (Y1).
[0182] [Example 1] Polypropylene (Prime Polypro F113G, manufactured by Prime Polymer Co., Ltd.) was molded into a film using a cast film molding machine equipped with a T-die at a cylinder temperature of 230° C. to obtain a cast film (substrate film I-1) having a thickness of 100 μm. The polypropylene used in the preparation of the base film I-1 had an MFR of 3.0 g / 10 min and a melting point (Tm) of 163° C. as measured by DSC.
[0183] Composition (X1) and adhesive composition (Y1) were mixed so that the liquid weight ratio was as shown in Table 2, and the applicator settings were adjusted so that the layer (II) had a dry thickness of 0.3 μm, and the mixture was applied to base film I-1. The applied mixture was uniformly spread with the applicator, and the laminate was dried at 100° C. for 20 seconds, and then aging treatment was performed for 20 hours at the temperature shown in Table 2 to obtain a laminate including base film (I) and layer (II).
[0184] [Example 2] Except for using composition (X2) instead of composition (X1), a laminate was produced and its physical properties were evaluated in the same manner as in Example 1. The obtained results are shown in Table 2.
[0185] [Example 3] Except for using the composition (X3) instead of the composition (X1), a laminate was produced and its physical properties were evaluated in the same manner as in Example 1. The obtained results are shown in Table 2.
[0186] [Example 4] Except for using the composition (X4) instead of the composition (X1), a laminate was produced and its physical properties were evaluated in the same manner as in Example 1. The obtained results are shown in Table 2.
[0187] [Example 5] Except for using composition (X5) instead of composition (X1), a laminate was produced and its physical properties were evaluated in the same manner as in Example 1. The obtained results are shown in Table 2.
[0188] [Example 6] A laminate was produced and its physical properties were evaluated in the same manner as in Example 2, except that the liquid weight ratio of the composition (X2) and the adhesive composition (Y1) was changed as shown in Table 2. The obtained results are shown in Table 2.
[0189] [Example 7] A laminate was produced and its physical properties were evaluated in the same manner as in Example 6, except that a base film I-2 obtained by subjecting base film I-1 to a corona treatment was used. The results are shown in Table 2.
[0190] [Example 8] A laminate was produced and its physical properties were evaluated in the same manner as in Example 2, except that the liquid weight ratio of the composition (X2) and the adhesive composition (Y1) was changed as shown in Table 2. The obtained results are shown in Table 2.
[0191] [Comparative Example 1] Except for using only the composition (X2) instead of the adhesive composition (Y1) in forming the layer (II), the laminate was produced and its physical properties were evaluated in the same manner as in Example 2. The obtained results are shown in Table 2.
[0192] [Comparative Example 2] Except for using composition (X5) instead of composition (X2), a laminate was produced and its physical properties were evaluated in the same manner as in Comparative Example 2. The obtained results are shown in Table 2.
[0193] [Comparative Example 3] Except for using only the adhesive composition (Y1) instead of the composition (X) in forming the layer (II), a laminate was produced and its physical properties were evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0194] [Comparative Example 4] A laminate was produced and its physical properties were evaluated in the same manner as in Example 7, except that the adhesive composition (Y1) was not used in forming the layer (II) and only the composition (X6) was used. The results are shown in Table 2.
[0195] [Comparative Example 5] The surface free energy was measured using only the base film I-1. The results are shown in Table 2.
[0196] [Surface free energy] Distilled water, diiodomethane, and bromonaphthalene were selected as liquids with different surface tensions, and the surface free energy was determined using these liquids. Specifically, 1.5 μL of the selected liquid was dropped onto the surface of layer (II) of the laminate at 23° C. and 50% RH, and the wetting state of the laminate 10 seconds after the liquid was dropped was analyzed using a DropMaster500 image processing solid-liquid interface analysis system (manufactured by Kyowa Interface Science Co., Ltd.) to determine the surface free energy (mN / m) of layer (II). The calculation theory was the extended Fowkes theory. In the case of Comparative Example 6, the surface free energy of the substrate film was determined.
[0197] [Evaluation of adhesion between substrate layer (I) and layer (II)] A test piece was prepared by marking the surface of the layer (II) of the obtained laminate with a grid in accordance with the method of the grid test described in JIS K5600. However, the number of grids was changed to 100, and the evaluation was performed as follows. An adhesive tape (Nichiban Co., Ltd., Cellotape (registered trademark)) was attached to the grid of the test piece, and then the tape was quickly pulled in a 60 degree direction to peel it off, and the number of grids that were not peeled off out of the 100 grids was counted to evaluate the adhesion between the base layer (I) and the layer (II). [Evaluation Criteria] A: The number of squares that were not peeled off was 100 B: The number of squares that were not peeled off is 50 to 99 C: The number of unpeeled squares is 49 or less
[0198] [Table 2] [Explanation of symbols]
[0199] 1: Laminate 10: Base material layer (I) 20,20A, 20B: Layer (II)
Claims
1. A substrate layer (I); a layer (II) containing a 4-methyl-1-pentene polymer (A) that satisfies the following requirements (a) to (c), and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A); A laminate comprising: (a) the melting point (Tm) measured by differential scanning calorimetry (DSC) is greater than 180°C and less than or equal to 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230° C. or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by a differential scanning calorimeter (DSC) is 210° C. or lower.
2. The laminate according to claim 1 , wherein the substrate layer (I) comprises a polyolefin having a melting point (Tm) of 200° C. or less as measured by a differential scanning calorimeter (DSC).
3. The laminate according to claim 2, wherein the polyolefin having a melting point (Tm) of 200° C. or less in the base layer (I) includes at least one selected from the group consisting of polypropylene and polyethylene.
4. 2. The laminate according to claim 1, wherein the surface free energy of the layer (II) on a surface opposite to the surface facing the base layer (I) is 32 mN / m or less.
5. The laminate according to claim 1 , wherein the olefin-based polymer (B) comprises an olefin-based thermoplastic elastomer.
6. 2. The laminate according to claim 1, wherein the layer (II) contains 100 to 4,000 parts by mass of the olefin polymer (B) based on 100 parts by mass of the 4-methyl-1-pentene polymer (A).
7. 6. The laminate according to claim 5, wherein a part or all of the olefin-based thermoplastic elastomer is a graft-modified olefin-based thermoplastic elastomer graft-modified with a polar group-containing monomer.
8. 2. The laminate according to claim 1, wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] of 0.5 to 5.0 dl / g as measured in decalin at 135° C.
9. The 4-methyl-1-pentene polymer (A) contains a structural unit (i) derived from 4-methyl-1-pentene, and, if desired, a structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), In the 4-methyl-1-pentene polymer (A), The content (U1) of the structural unit (i) is 84 to 100 mol %, The content (U2) of the structural unit (ii) is 0 to 16 mol% (wherein the total of U1 and U2 is 100 mol%). The laminate according to claim 1 .
10. 10. The laminate according to claim 9, wherein the structural unit (ii) is a structural unit derived from an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).
11. The laminate according to claim 3, wherein the polyolefin having a melting point (Tm) of 200° C. or less in the base layer (I) includes polypropylene.
12. A step of preparing a base film and a composition containing a 4-methyl-1-pentene polymer (A) and an olefin polymer (B) other than the 4-methyl-1-pentene polymer (A), which satisfy the following requirements (a) to (c): applying the composition to a surface of the substrate film; A step of subjecting the substrate film coated with the composition to an aging treatment in an environment of less than 80° C. for 72 hours or less; A method for producing a laminate, comprising: (a) the melting point (Tm) measured by differential scanning calorimetry (DSC) is greater than 180°C and less than or equal to 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230° C. or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by a differential scanning calorimeter (DSC) is 210° C. or lower.
Citation Information
Patent Citations
Composition, film, and method for producing the film
JP2015034258A
Film and method for producing film
JP2023073865A